Effect of Dietary Supplementation of Organic Acids on Performance, Nutrients Digestibility and Health of Broiler Chicks - Ghazalah, A.A.; Atta, A.M.; Elkloub, Kout; Moustafa, M.EL.; Shata , Riry F.H. (International Journal of Poultry Science, 2011)
This study was conducted to compare the effects of different types and levels of organic acids being Formic (0.25, 0.5 and 1.0% FA), Fumaric (0.5, 1.0 and 1.5% FUA), Acetic (0.25, 0.50 and 0.75% AC) and Citric Acids (1, 2 and 3% CA). A total number of 351 one d-old Arbor-Acres broiler chicks were randomly divided into 13 treatment groups, each in three replicates of 9 chicks per replicate. The first group was fed the basal diet without supplementation and served as control. While, the other groups were received the basal diet supplemented with the tested organic acids. The experiment was lasted when chicks were 42 d old. Performance, pH of some gastrointestinal tract (GI-tract) segments, organ morphology, cecal bacteria, blood metabolites and nutrients digestibility were measured. Results obtained could be summarized as follow: 1- Any of the tested organic acids increased significantly (p<0.01) body weight gain and European Production Efficiency Index compared with the control group. However, feed conversion ratio improved, but not significantly in case of formic and fumaric acids, while significantly improved with acetic and citric acids supplementation, compared to the control. No great differences in mortality rate were observed among all treatments as from 1 to 2 birds were died all over the experimental period due to natural causes and not due to nutritional treatments. 2- Dietary organic acids improved both ME and nutrients digestibility of the experimental diets compared to the control. 3- Dietary organic acids significantly reduced (p<0.01) the pH values in the different GI-tract segments of the chicks compared to chicks fed the control. 4- Feeding dietary FA and FUA led to sharp reduction in caeca content of lactobacilli bacteria, but increased number of coliforms bacteria and anaerobes was slightly increased. Feeding 0.75% AC and 2%CA increased Lactobacillus count and coliforms. Villus height was significantly higher (p<0.01) of all organic acid supplementation fed groups. 5- Blood serum content of calcium, phosphorus, total protein and globulin were increased significantly (p<0.01) by 0.5% FA, 0.5% FUA, 0.75% AC and 2%CA in the diet compared to the control. 6- Relative weights of lymphoid organs (spleen, bursa of fabrics and thymus gland) were significantly higher (p<0.01) by supplementing the tested organic acids compared to the control group. In conclusion, dietary 0.5% either of formic or fumaric as well as 0.75% acetic or 2% citric acids could be used safely to improve performance and health of broiler chickens.